Bioimpedance body composition tests in golfers` annual training cycle - Baymukhametova, E. F.; Nenasheva, A. V.; Aminov, A. S. (Theory and Practice of Physical Culture, 2019)
The study analyzes benefits of the bioimpedance body composition tests for the 13-14 year-old golfers` of both sexes under the physical education curricula. Body composition was tested by Tanita BC-418 MA Body Composition Analyzer designed based on the innovative technology of measurement of impedance (electrical resistance) of the body. Physical development of the sample was estimated by the body/ limb fat mass indices and total water level, with the study data processed by a standard statistical toolkit.